Avaliação Histológica da População de Folículos Pré-Antrais Ovarianos e da Taxa de Atresia Folicular em Fêmeas de diferentes espécies e Posições Hierárquicas de Leontopithecus Sp. (Callitrichidae Primates) mantidas em Cativeiro - Brasil, Alline Ferreira (2008)
Knowledge about the preantral folliculogenesis of tamarins (Leontopithecus sp) are scarce. The present study aimed to obtain quantitative and qualitative data about the follicular ovarian population in Lion tamarin females from different species (L. rosalia, L. chrysomelas, L. chrysopygus) and hierarchical status (non-dominant female, dominant female and subordinate female). Fiveteen ovaries were obtained from each adult female group (non-dominant female, dominant female and subordinate female). The ovaries were divided in 2 halves and one of that was destined for classic histology. Each half was sectioned serially at a thickness of 5 µm and each 10 th section of ovarian tissue fragment was mounted and stained with periodic acid Schiff and hematoxylin (PAS- Hematoxylin).There was statistical difference between the right and left ovaries for the follicular population. The right ovary had a larger follicular population compared to the left in Lion tamarin females from different species and hierarchical status. Concerning the percentage of follicles by follicular category, in the present study a larger percentage of primary follicles was found in relation to the other preantral follicles. The percentage of normal follicles was significantly greater than the percentage of degenerate follicles in all categories in Lion tamarin females from different species and hierarchical status. The greatest percentage of degenerate preantral follicles was the primordial. Non-dominant female and subordinate female showed a larger percentage of degenerate follicles in relation of dominant female. Statistical difference found in the follicular diameter in three species of Leontopithecus show that is possible to use it to aid in the classification of the different follicular categories. We conclude that the information obtained in this study can be used as a parameter for subsequent in vivo or in vitro studies about folliculogenesis in non-human neotropical primates of the Leontophitecus species